Headache and Comorbidities in Childhood and Adolescence - Guidetti, Vincenzo; Arruda, Marco A.; Ozge, Aynur (Headache,, 2017)
This book aims to provide clinicians and other practitioners and professionals with up-to-date information on how to evaluate and manage headaches in children and adolescents, highlighting the most recent recommendations. Unlike in other books on the subject, detailed attention is devoted to the various comorbidities commonly associated with headache, including psychiatric comorbidities such as depression, anxiety, attention deficit hyperactivity disorder, and learning disabilities and medical conditions such as epilepsy, vascular disorders, brain tumors, atopic disease, and obesity. The intimate link between these conditions and headache is explained with a view to enabling the reader to recognize their presence and, on that basis, to institute the most effective pharmacological or non-pharmacological treatment strategy. Moreover, knowledge of the comorbidities associated with headache will help readers to understand more fully the causes of this serious disorder and also its consequences, e.g., for school performance, relationships, and daily activities. The authors are all international experts who care for children with headache or the other described disorders.